2003
DOI: 10.1103/physrevlett.90.044101
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chaos Triggered by Precursors of a Quantum Phase Transition: The Dicke Model

Abstract: We consider the Dicke Hamiltonian, a simple quantum-optical model which exhibits a zerotemperature quantum phase transition. We present numerical results demonstrating that at this transition the system changes from being quasi-integrable to quantum chaotic. By deriving an exact solution in the thermodynamic limit we relate this phenomenon to a localisation-delocalisation transition in which a macroscopic superposition is generated. We also describe the classical analogues of this behaviour.At zero temperature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
699
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(739 citation statements)
references
References 33 publications
37
699
2
1
Order By: Relevance
“…In order to describe excitations in the parameter region above the critical point, we now incorporate the fact that both the field and the atomic collective excitations acquire macroscopic occupations, namely, the above approximation to neglect the number of excitations over N is no longer valid [2]. To this aspect, the introduced collective operators B † and C † in Eq.…”
Section: Super-radiant Phasementioning
confidence: 99%
See 2 more Smart Citations
“…In order to describe excitations in the parameter region above the critical point, we now incorporate the fact that both the field and the atomic collective excitations acquire macroscopic occupations, namely, the above approximation to neglect the number of excitations over N is no longer valid [2]. To this aspect, the introduced collective operators B † and C † in Eq.…”
Section: Super-radiant Phasementioning
confidence: 99%
“…where α, β and γ are generally complex parameters in the order of O( √ N ) [2] to be determined later. This is equivalent to assume that all modes behave as the nonzero, macroscopic mean fields above λ (n) c .…”
Section: Super-radiant Phasementioning
confidence: 99%
See 1 more Smart Citation
“…It was later found that in the thermodynamical limit, i.e., the atom number N → ∞, and in the strong-coupling regime, the model exhibits a superradiant quantum phase transition (QPT) [10][11][12][13][14][15][16]. In a large N limit and a single-qubit coupling strength beyond the critical point, the effective coupling between atoms and the radiation mode becomes comparable to the bare frequencies of the atom and radiation mode, which leads to the occurrence of a superradiant phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate it we selected the Dicke model that proved to be very useful in studying quantum optical [34][35][36][37][38], chaotic [38,39] or entanglement [40] properties. It has been realized with a superfluid gas in an optical cavity [41] and the spontaneous symmetry breaking has been observed recently [42].…”
Section: Introductionmentioning
confidence: 99%